Metabolomics approach to identify key volatile aromas in Thai colored rice cultivars - Tansawat, Rossarin; Jindawatt, Supawat; Ekkaphan, Paweena; Ruengphayak, Siriphat; Vanavichit, Apichart; Suttipanta, Nitima; Vimolmangkang, Sornkanok; De-Eknamkul, Wanchai (Frontiers in Plant Science, 2023)
In addition to white jasmine rice, Thailand has many native-colored rice varieties with numerous health benefits and the potential to become a global economic crop. However, the chemical characteristics of aromatic substances in native-colored rice are still mostly unknown. This study aimed to identify the key volatile aroma compounds and the biosynthetic pathways possibly involved in their formation in Thai native-colored rice varieties, and thus leading to the search for potential genetic markers for breeding colored rice with better aromatic properties. Twenty-three rice varieties in four categories: aromatic white, aromatic black, non-aromatic black, and non-aromatic red, were investigated (n=10 per variety). Seed husks were removed before the analysis of rice volatile aromas by static headspace gas chromatography–mass spectrometry. Untargeted metabolomics approach was used to discover the key volatile compounds in colored rice. Forty-eight compounds were detected. Thirty-eight of the 48 compounds significantly differed among groups at p<0.05, 28 of which at p<0.0001, with the non-aromatic black and red rice containing much lower content of most volatile constituents than the aromatic black and white rice. Focusing on the aromatic black rice, the samples appeared to contain high level of both compound groups of aldehydes (3-methylbutanal, 2-methylbutanal, 2-methylpropanal, pentanal, hexanal) and alcohols (butane-2,3-diol, pentan-1-ol, hexan-1-ol). Biosynthetically, these distinctive black-rice volatile compounds were proposed to be formed from the metabolic degradation of branched-chain amino acids (L-leucine, L-isoleucine and L-valine) and polyunsaturated fatty acids (linoleic acid and α-linolenic acid), involving the branched-chain aminotransferases and keto-acid decarboxylases and the 9-lipoxygonases and 13-lipoxygeases, respectively. The proposed degradative pathways of amino acids and fatty acids were well agreed with the profiles key volatile compounds detected in the Thai native-colored rice varieties.